«Pachamama no te cuido» - Avalo, Ana Valeria (2024)
The objective of this article is to analyze the articulation between neo-extractivist policies and neo-indigenist policies in Jujuy, Argentina, between the years 2015 and 2022. Specifically, we study the articulation of the Secretariat of Indigenous Peoples with other spheres of the provincial State and with indigenous communities. We address three cases: the sanction of Law 5915 in 2016, the creation of the Intercultural Police in 2018, and the project to install the Free Zone in Quiaca Vieja (department of Yavi, Puna region) in 2018-2022. We hold as a hypothesis that the indigenist institutionality operates to legitimize the neo-extractivist economic policy that is presented as a renewal of the productive matrix. We return to a qualitative methodology and use documentary review and interviews with key informants as data construction techniques. Our theoretical framework includes critical perspectives on neo-extractivism and neo-indigenism, as well as contributions from Indian-indigenous political thought.